2009
DOI: 10.5433/1679-0359.2009v30n1p225
|View full text |Cite
|
Sign up to set email alerts
|

Policultivo do camarão de água doce Macrobrachium amazonicum (Heller, 1862) com a Tilápia do Nilo (Oreochromis niloticus) alimentadas com rações peletizada e farelada

Abstract: Foram utilizadas 30 tilápias e 150 camarões por unidade experimental distribuídos em um delineamento inteiramente ao acaso com 4 tratamentos e 4 repetições, sendo TF: tilápia alimentadas com ração farelada; TCF: tilápia e camarão alimentados com ração farelada; TP: tilápia alimentada com ração peletizada e TCP: tilápia e camarão alimentados com ração peletizada. A densidade utilizada foi de 2,6 peixes/m 2 com peso inicial médio de 5,58 ± 0,10 g e comprimento inicial médio de 5,56 cm, sendo a densidade de camar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 3 publications
1
5
0
4
Order By: Relevance
“…The survival of prawns during the study was higher than the values from 40 to 60% reported by Wichins & Lee (2002) with the genus Macrobrachium in semiintensive crops in excavated ponds. However, our results were similar to those found by Souza et al (2009) in a polyculture of M. amazonicum and Oreochromis niloticus, ranging from 71.5 to 77%. Preto et al (2008) tested the feeding trays for M. amazonicum and recorded an average survival of 85.8%.…”
Section: Discussionsupporting
confidence: 91%
“…The survival of prawns during the study was higher than the values from 40 to 60% reported by Wichins & Lee (2002) with the genus Macrobrachium in semiintensive crops in excavated ponds. However, our results were similar to those found by Souza et al (2009) in a polyculture of M. amazonicum and Oreochromis niloticus, ranging from 71.5 to 77%. Preto et al (2008) tested the feeding trays for M. amazonicum and recorded an average survival of 85.8%.…”
Section: Discussionsupporting
confidence: 91%
“…Prawn cultured in BFT showed WG 65.4% superior in comparison to RAS. According to Souza et al (2009), freshwater prawn Macrobrachium amazonicum (Heller 1862) did not influence the growth of Nile tilapia in polyculture in RAS. However, in the present study, polyculture with tilapia and giant freshwater prawn boosted the growth performance both BFT and RAS for these two species.…”
Section: Discussionmentioning
confidence: 99%
“…Tilapia-shrimp or tilapia-prawn polyculture adoption has been expanded among producers in many countries, and some studies have been conducted to test the efficiency of these systems (Candido et al, 2005;Tendencia et al, 2006Tendencia et al, , 2011Muangkeow et al, 2007;Uddin et al, 2007Uddin et al, , 2009El-Sherif & Ali Mervat, 2009;Souza et al, 2009;Martínez-Porchas et al, 2010;Yuan et al, 2010;Shahin et al, 2011;Bessa Junior et al, 2012).…”
Section: Introductionmentioning
confidence: 99%